STUDI KASUS PERAN PENGGUNAAN QR CODE SEBAGAI PENGGANTI FILM HASIL RADIOGRAF DI INSTALASI RADIOLOGI RS ISLAM SUNAN KUDUS - Sylvia (Universitas Aufa Royhan, 2025)
Technological developments encourage changes in the field of radiology. Radiograph results given to patients generally use film but in the Radiology Installation of Sunan Kudus RSI uses a QR Code. The research objectives discuss the advantages and disadvantages of the QR Code. The type of research used is descriptive qualitative research with a case study method. The place of research was at the Radiology Installation of RSI Sunan Kudus. The research time was September 2024 to January 2025. Data collection includes observation, interviews, documentation and literature study. The population includes all medical personnel and patients in the radiology installation. The sample included 1 Head of the Radiology Room and 6 patients with age categories of adolescents, adults, and elderly with purposive sampling technique. Data analysis includes data collection, data presentation and conclusion drawing. The results of the study show that changes in the flow of services are digitized by computerization with SIMRS and ERM connected to RIS and PACS. The results of the interview show that the application of the QR Code in the Radiology Installation of RSI Sunan Kudus can increase the efficiency of service time, save film expenditure costs and save storage shelves. However, there are still obstacles such as difficulty accessing images, waiting time for CT-Scan image results, use of printed ultrasound films and certain patient categories. The suggestion in this study is that the application of this QR Code can be updated later, the service flow can be extended, printed films are available for patients with special needs, so that the application of this technology can be more optimal.